2017
DOI: 10.1016/j.jnoncrysol.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic glass transition of filled polysiloxane upon electron irradiation

Abstract: a b s t r a c tThe influence of radiation-induced crosslinking on the molecular mobility of a filled silicone elastomer near the glass transition (α-relaxation) was analyzed using broadband dielectric spectroscopy. Samples of the isolated polysiloxane matrix (neat) were also studied so as to assess the filler influence on the evolution of the αrelaxation. A slowing-down of the segmental dynamics was observed with increasing ionizing dose. It was ascribed to the relaxing dipoles losing degrees of freedom as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…This trend has been observed on several space used polymers (silicon, PEEK, FEP, ETFE, …) and is usually due to crosslinking effects together with the creation of new chemical bonds that reduce molecular mobility and charge transport. This conductivity decrease has been demonstrated through different in-situ and ex-situ measurements and a former study performed on space used silicons proved also a steep decline of conductivity [16,17]. On the contrary, Kapton ® wires tends to get more conductive with the increasing radiation dose (for doses lower than 10 6 Gy): this result confirms previous studies on Kapton ® HN on which we observed the same trend.…”
Section: Analysis Of Cumulative Effect Of Radiation Dosesupporting
confidence: 90%
“…This trend has been observed on several space used polymers (silicon, PEEK, FEP, ETFE, …) and is usually due to crosslinking effects together with the creation of new chemical bonds that reduce molecular mobility and charge transport. This conductivity decrease has been demonstrated through different in-situ and ex-situ measurements and a former study performed on space used silicons proved also a steep decline of conductivity [16,17]. On the contrary, Kapton ® wires tends to get more conductive with the increasing radiation dose (for doses lower than 10 6 Gy): this result confirms previous studies on Kapton ® HN on which we observed the same trend.…”
Section: Analysis Of Cumulative Effect Of Radiation Dosesupporting
confidence: 90%
“…Finally, the study of the α relaxation loss permittivity peak width can also provide information about the environment close to relaxing entities [2]. In this way, the loss permittivity peaks have been recalculated for each type of samples using the imaginary part of equation 6, which is developed in [21], and the Havriliak-Negami parameters obtained by the fit of α relaxation.…”
Section: α Relaxationmentioning
confidence: 99%
“…The first one is due to low-energy electrons which induce electrical charging of polymer surface and lead to electrostatic discharge phenomena responsible of many spacecraft failures [1]. The second one is due to high-energy electrons which depose energy in polymer volume and induce different phenomena like physico-chemical ageing [2,3] or radiation-induced conductivity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…According to Figure 8a, the time affects the dielectric loss of PDMS_oil/0 by a small decrease of the relaxation peak around 0.1 MHz and a shift of that peak towards lower frequencies. This relaxation peak is associated with the chain mobility, and therefore, the shift may be explained by a small increase in the degree of crosslinking [43,44]. More significantly, the losses associated with the DC-conductivity are reduced with time, and the largest loss reduction is visible between 1 day and 2 months.…”
Section: Resultsmentioning
confidence: 99%